A model for lubricated revolute joints in multibody mechanical systems - Flores, Paulo (2005)
The main purpose of this work is to present a general methodology for modeling lubricated revolute joints in constrained multibody systems. In the dynamic analysis of journal-bearings, the hydrodynamic forces, which include both squeeze and wedge effects, generated by the lubricant fluid, oppose to the journal motion. The hydrodynamic forces are obtained by integrating the pressure distribution evaluated with the aid of Reynolds’ equation written for the dynamic regime. The hydrodynamic forces built up by the lubricant fluid are evaluated from the state of variable of the system and included into the equations of motion of the mechanical system. Numerical examples are presented in order to demonstrate the efficiency and accuracy of the methodologies and procedures adopted.